Studies on Phenylating SBA-15 Material - Zhai, Qing-Zhou; Yang, Dong (Asian Journal of Chemistry, 2010)
Benzene (Ph) functionalized mesoporous molecular sieve of SBA-15 [Ph-(SBA-15)] was synthesized by post-synthesis method using phenyltriethoxysilane as coupling agent. The products were characterized by means of element analysis, powder X-ray diffraction, infrared spectroscopy, low-temperature nitrogen adsorption-desorption technique, transmission electron microscopy, thermogravimetry-differential thermal analysis. The results showed that phenyl was successfully grafted to the mesoporous molecular sieve SBA-15. The Ph-(SBA-15) mesoporous molecular sieve still retained the ordered mesoporous structure and possesses high thermal stability.